2003
DOI: 10.3748/wjg.v9.i1.125
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine attenuates alcohol-induced oxidative stress in the rat

Abstract: AIM:There is increasing evidence that alcohol-induced liver damage may be associated with increased oxidative stress. We aimed to investigate free-radical scavenger effect of nacetylcysteine in rats intragastrically fed with ethanol. METHODS:Twenty-four rats divided into three groups were fed with ethanol (6 g/kg/day, Group 1), ethanol and nacetylcysteine (1 g/kg, Group 2), or isocaloric dextrose (control group, Group 3) for 4 weeks. Then animals were sacrificed under ether anesthesia, intracardiac blood and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 31 publications
(30 reference statements)
4
45
1
2
Order By: Relevance
“…The protective effects of NAC could be also explained by the fact that it is required for glutathione biosynthesis, thus inhibiting ROS toxicity (35). Additionally, it was de mon strated that alcohol-induced oxidative stress could be inhibited by NAC administration (36,37). More over, it was showed that in fact NAC intake and ethanol abstinence interact synergistically in order to improve the hepatic antioxidant defenses and to decrease the serum lipids concentrations (37).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of NAC could be also explained by the fact that it is required for glutathione biosynthesis, thus inhibiting ROS toxicity (35). Additionally, it was de mon strated that alcohol-induced oxidative stress could be inhibited by NAC administration (36,37). More over, it was showed that in fact NAC intake and ethanol abstinence interact synergistically in order to improve the hepatic antioxidant defenses and to decrease the serum lipids concentrations (37).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol causes elevation in the level of NADH in mitochondria which further causes an increase in number of superoxide free radicals leaked from oxidative phosphorylation leading to formation of hydroxyl radicals and depleted activities of antioxidant enzymes. [24][25] Antioxidant enzymes viz; CAT, POD, GST, GPx was significantly (P<0.05) decreased in ethanol treated rats group which were recovered by co-administration of 200 mg/kg b.w., AJME significantly (P<0.05) and increased the activity to normal level. Similar reports were obtained by other study.…”
Section: Discussionmentioning
confidence: 99%
“…Acute alcohol intoxication or chronic alcoholism leads to renal damage. Protein deficiency and enzyme activity impairment with a decreased concentration of serum albumin and alteration in enzyme activities have also been associated with alcoholic liver disease (ALD) (Ozaras et al, 2003).…”
Section: Introductionmentioning
confidence: 99%